EFEKTIVITAS BADAN PENYELESAIAN SENGKETA KONSUMEN KOTA PEKANBARU - Wenny Mulsandi; Chalid Sahuri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
An imbalance position of consumers and businesses both in terms of economic and technical, so need to be bridged through a variety of efforts, including through consumer protection movement. Createda variety of institutional and legal devices and other effortsaimedat making consumer consumes the goods/services they want in a safe and protected, One Consumer Dispute Settlement Board (BPSK) Pekanbaru City. Consumer Dispute Settlement Board of Pekanbaru the independent agency, created by –Undang Law No. 8 of 1999 on Consumer Protection, RI Presidential Decree No.23 of 2006, and KEPMEN of Industry and Trade Decree No.350/MPP/Kep/12/2001. But the Consumer Dispute Settlement Board Pekanbaru Cityis not maximized their duties. It isevident from the many people who do not know where the Agency hasestablished 6 years ago.Yet the number of tasks completed because of blocked funds operational problems, unstable management practices, as well as the lack of attention to Human Resources who runs the Consumer Dispute Settlement Body of Pekanbaru. The problem in this study is how the effectiveness of the Consumer Dispute Settlement Board (BPSK) Pekanbaru City and the factors that affect the effectiveness of the Consumer Dispute Settlement Board (BPSK) the Pekanbaru City. The purpose of this study was to determine the condition of the effectiveness of the Consumer Dispute Settlement Board (BPSK) Pekanbaru City and to determine the factors that affect the effectiveness of the Consumer Dispute Settlement Board (BPSK) Pekanbaru City.The concept ofthe theoryisthat researchers use effectiveness,organizational and institutional development. This study uses qualitative research methods to study descriptive data. In collecting the data, the researcher used interview, observation and documentation. By using key informantsas a sourceof information.The results of this study indicate that the effectiveness of the Agency for Consumer Disputes ettlement has not been effective Pekanbaru City, seen from the stage of effectiveness are not met, in which only the input stage and the absence of immediate results (outputs). The factors that influence the effectiveness of the Consumer Dispute Settlement Board of Pekanbaru the ability to adapt, work productivity, job satisfaction, and utilization of resources (human resource capacity).keyword: Effectiveness, ConsumerDisputes, Consumer Dispute Settlement Board of Pekanbaru